Bivalve Abundance and Distribution in the Seaweed Ecosystem in the Waters of Jago-Jago Village, Tapanuli Tengah, North Sumatra Province - Siagian, Yosua; Zulkifli, Zulkifli; Tanjung, Afrizal (Journal of Coastal and Ocean Sciences, 2024)
This research was conducted in May 2022. This research was conducted in Jago-jago Village, Tapanuli Tengah, North Sumatra Province. The aim was to determine the abundance and distribution pattern of bivalves in the study area. The method used in this study is a survey method, namely direct observation, taking samples in the field, and then analyzing them in the laboratory. Determining observation stations and data collection using the purposive sampling method is done by considering various conditions at the research location. Sampling was carried out at three stations that were considered representative of the research area. Each station consists of 3 transects with a length of 50 m each, where each transect has three plots measuring 1x1m2. From the research results of the types of bivalves found in the coastal waters of Jago-Jago Village during the study, there were six types of families, namely Arcidae, Cardiidae, Mesodesmatidae, Ostreidae, Donacidae, and Corbiculidae. At the same time, there were as many as six species: Anadara antiquata, Trachycardium subrugosum, Atactodea sp, Crassostrea sp, Donax sp, and Polymesoda erosa. Based on the results of the ANOVA test, it was known that the abundance of bivalves in the coastal waters of Jago-Jago Village showed a significant value obtained <0.05, namely 0.016. This indicates that the difference in abundance between stations is significantly different. The average organic matter content at station 1 is 4.59%. The substrate is muddy sand with an abundance value of 4.33 ind/m2. At station 2, the organic matter content is 4.05% with sand substrate, and the abundance value is 3.11 ind/m2. The organic matter content at station 3 is a 6.39% sandy mud substrate with an abundance value of 6.11 ind/m2. The highest relative abundance of bivalves found at station 3 was Donax sp, which is 32.72%.